Late prehistory and protohistory : Bronze Age and Iron Age : proceedings of the XVII UISPP World Congress (1-7 September 2014, Burgos, Spain). - Coimbra, Fernando,; Delfino, Davide, 1976-; Sîrbu, Valeriu, 1950-; Schuster, Cristian, (Archaeopress Archaeology, 2016)
This work contains the proceedings of two sessions from the XVII UISPP World Congress, 2014.